(untitled) (Journal of the College of Basic Education, 2023)
The television advertisement is one of the most important contents on the television screens.Not only because of the nature of advertising and its ethical issues, but because of the role it plays in achievingAdvertising income used by radio and television stations to finance their activities and programs.different.Commercial advertising is witnessing multiple developments at the world level, benefiting fromTechnological developments brought about by the Internet and the growing commercial trend in the means ofglobal media, and this matter extended to the so-called Sponsored programmes.(Programs) Some advertising choices also appeared on the part of some of those who sponsorPrograms that have a large audience (1).Advertising has become an integral part of our daily lifeterrestrial and satellite television to a large extent, and despite some legislationrules in media institutions, but the reality shows that they are insufficient or not adhered to.at the level of application and implementation, either due to the lack of awareness of the seriousness of the declaration, or in pursuit of achievingThe highest financial returns (2). Some believe that the privatization of media activity in the country